Pearl Jam twenty [videorecording (DVD)] - Crowe, Cameron, 1957-; Crowe, Cameron, 1957-; Crowe, Cameron, 1957- (Distributed by Columbia Records, 2011)
In honor of Pearl Jam's twentieth anniversary, Academy Award-winning director and music journalist Cameron Crowe created a definitive portrait of the seminal band: part concert film, part intimate insider-hang, part testimonial to the power of music and uncompromising artists.